In Higher Mathematics: The analytics of connected learning and MATLAB online - Basantes-Valverde, Williams; Maldonado-Chávez, Vinicio; Allauca-Sandoval, Norma (Educación y sociedad, 2024)
This investigation is the foundation of a project related to the teaching of the subject Mathematical Programming. Said work is limited to the investigations carried out in the Digital Education Specialty and based on them it was possible to create structural models as a foundation for the Connected Learning Analytics. Where the basic principles of mathematical programming are outlined through a predictive analysis plan and existing academic doubts between teacher and student are clarified with the use of technology; at the same time projected as solutions. However, this is the beginning of the construction of knowledge for future Engineers. Since, unfortunately, this methodological adaptation is not always assumed by the teachers who take the subjects of Exact Sciences. Reason for this, this time the online update paradigm and one of its key tools have been chosen: MATLAB.